Rosacea-like cystic acne. - Milano, A. (European Journal of Pediatric Dermatology, 2013)
In our patient the diagnosis of rosacea was ruled out due to the onset almost contemporary to menarche, the presence of comedones and elongated nodules of cystic appearance and the lack of ocular signs; the negative fresh examination for Demodex and especially the rapid response to treatment with isotretinoin confirmed the diagnosis of cystic acne. Isotretinoin had been also effective in some rare forms of rosacea clinically different from our case, in the presence of sebaceous gland hyperplasia (2) or Morbihan disease (1). Morbilhan disease, also known as granulomatous or lymphedematous rosacea, is a rare complication of rosacea, which occurs in adults with persistent edema of the upper half of the face, little or nothing responsive to therapy. Some cases of Morbilhan disease which did not respond to other therapies were treated with isotretinoin for long periods of time with some success.